Hypercalcemia Is a Risk Factor for the Progression of Aortic Calcification in Kidney Transplant Recipients - Toshihide Naganuma; Yoshiaki Takemoto; Junji Uchida; Tatsuya Nakatani; Daijiro Kabata; Ayumi Shintani (Karger Publishers, 2019)
Background/Aims: Vascular calcification is common and progressive in chronic kidney disease, including kidney transplant recipients (KTRs). However, the risk factors associated with the progression of aortic calcification (AoC) in KTRs have not been fully elucidated. In the present study, we evaluated AoC and examined the factors associated with its advancement in KTRs. Materials: This was a prospective longitudinal study that included 98 KTRs. We quantitatively investigated infrarenal abdominal AoC using the Agatston score, as measured by multi-slice computed tomography. After the baseline investigation, a follow-up scan was performed after 3 years, and the Agatston scores were obtained again. The changes in laboratory data affecting the 2nd Agatston scores were examined by multivariable analysis using non-linear regression after adjustment for several confounders. Results: The 2nd Agatston scores were significantly greater than the baseline Agatston scores (p < 0.001). After adjustment for the confounders, the change in corrected serum calcium exhibited a significant non-linear correlation with the 2nd Agatston scores (p = 0.022 for non-linearity/p = 0.031 for the effect of corrected serum calcium). Moreover, an interaction was present from the baseline AoC in the effect of corrected serum calcium on the progression of AoC, and the effect of hypercalcemia was greater in patients with higher baseline Agatston scores (p = 0.049). Conclusion: The present study revealed that hypercalcemia is a risk factor for the development of infrarenal abdominal AoC in KTRs. Furthermore, the effect of hypercalcemia was greater in patients with more severe vascular calcification.